2011
DOI: 10.4028/www.scientific.net/amm.55-57.392
|View full text |Cite
|
Sign up to set email alerts
|

Study on Properties of Recycled Fiber from Waste Newspaper / PLA Composites

Abstract: Prepare composite materials with recycled fibers from waste newspaper and PLA by inject-molding process, and study on recycled fiber of the modified-property treatment of silane coupling agent and alkali deinking treatment influence properties of composite materials. It is found out that, recycled fibers under the modified-property treatment of silane coupling agent and under alkali deinking treatment can effectively improve compatibility between recycled fibers and PLA, and improve mechanical properties and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Nagarajan et al 28 prepared cellulose nanomaterials from used disposal paper cups, while Silva et al 29 used coffee grounds oil to produce radiolytic stabilized PVC. Likewise, Tong et al 30 studied the properties of recycled fiber from waste newspaper/PLA composites. It was reported that the modification of the fibers using alkali treatment effectively improved the compatibility between fibers and PLA, the mechanical properties and water absorbency of composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nagarajan et al 28 prepared cellulose nanomaterials from used disposal paper cups, while Silva et al 29 used coffee grounds oil to produce radiolytic stabilized PVC. Likewise, Tong et al 30 studied the properties of recycled fiber from waste newspaper/PLA composites. It was reported that the modification of the fibers using alkali treatment effectively improved the compatibility between fibers and PLA, the mechanical properties and water absorbency of composite materials.…”
Section: Introductionmentioning
confidence: 99%